Memory impairment is associated with the loss of regular oestrous cycle and plasma oestradiol levels in an activity-based anorexia animal model. (18th May 2016) - Paulukat, Lisa; Frintrop, Linda; Liesbrock, Johanna; Heussen, Nicole; Johann, Sonja; Exner, Cornelia; Martien, Kas J.; Tolba, Rene; Neulen, Joseph; Konrad, Kerstin; Herpertz-Dahlmann, Beate; Beyer, Cordian; et al.
Abstract: Objectives: Patients with anorexia nervosa (AN) suffer from neuropsychological deficits including memory impairments. Memory partially depends on 17β-oestradiol (E2), which is reduced in patients with AN. We assessed whether memory functions correlate with E2 plasma levels in the activity-based anorexia (ABA) rat model.Methods: Nine 4-week-old female Wistar rats were sacrificed directly after weight loss of 20 – 25% (acute starvation), whereas 17 animals had additional 2-week weight-holding (chronic starvation). E2 serum levels and novel object recognition tasks were tested before and after starvation and compared with 21 normally fed controls.Results: Starvation disrupted menstrual cycle and impaired memory function, which became statistically significant in the chronic state (oestrous cycle ( P  < 0.001), E2 levels ( P  = 0.011) and object recognition memory ( P = 0.042) compared to controls). E2 reduction also correlated with the loss of memory in the chronic condition ( r  = 0.633, P = 0.020).Conclusions: Our results demonstrate that starvation reduces the E2 levels which are associated with memory deficits in ABA rats. These effects might explain reduced memory capacity in patients with AN as a consequence of E2 deficiency and the potentially limited effectiveness of psychotherapeutic interventions in the starved state. Future studies should examine whether E2 substitution could prevent cognitive deficits and aid in earlier readiness for therapy.